Enhancing Neuroanatomy Teaching with DSI Studio’s Fiber Reconstruction Technology - Zeng J; Shi L; Liu Y; Yang J; Zhang L; Song H; Zhao Y; Yang J; Cheng X; Lu L (Advances in Medical Education and Practice, 2025)
Junfeng Zeng,1 Lihong Shi,1 Yongbo Liu,2 Jian Yang,3 Luqing Zhang,4 Huifang Song,1 Yunhe Zhao,1 Jing Yang,1 Xiaolong Cheng,5 Li Lu1,6 1School of Basic Medical Sciences, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 2Department of Radiology, Peking University Care Lu’an Hospital, Changzhi, Shanxi, People’s Republic of China; 3School of Biomedical Sciences, The University of Hong Kong, People’s Republic of China; 4School of Basic Medical Sciences, Nanjing University, Nanjing, Jiangsu, People’s Republic of China; 5Science and Technology Department, The Second Hospital of Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of China; 6Key Laboratory of Cellular Physiology of Chinese Ministry of Education, Shanxi Medical University, Taiyuan, Shanxi, People’s Republic of ChinaCorrespondence: Li Lu, School of Basic Medical Sciences, Shanxi Medical University, Key Laboratory of Cellular Physiology of Chinese Ministry of Education, Taiyuan, Shanxi, 030001, People’s Republic of China, Email luli@sxmu.edu.cn Xiaolong Cheng, Science and Technology Department, The Second Hospital of Shanxi Medical University, Taiyuan, Shanxi, 030001, People’s Republic of China, Email chengxl@sxmu.edu.cnBackground: DSI Studio is an advanced imaging software specifically designed for the analysis of diffusion magnetic resonance imaging (dMRI). Its key features, which include fiber reconstruction, fiber tracking, and 3D visualization, have established its significant role in neuroscience research.Objective: A solid understanding of spatial relationships is crucial for students studying anatomy. However, there has been limited research in Chinese medical education regarding the integration of 3D imaging technology into anatomical instruction. To address this gap, we conducted an innovative study utilizing DSI Studio to enhance neuroanatomy education.Methods: An innovative study was conducted utilizing DSI Studio for fiber reconstruction and 3D visualization in neuroanatomy workshops. A total of 38 students participated in hands-on sessions, with 13 completing pre-training surveys and 19 completing post-training surveys. The students’ understanding of neuroanatomy prior to training, as well as their performance and experiences during the neuroanatomy learning process, were systematically recorded. Additionally, the effectiveness of DSI Studio software in enhancing neuroanatomy learning was assessed in conjunction with the reconstruction capabilities of the software.Results: The application of DSI Studio significantly improved students’ visualization of neural structures, surpassing traditional teaching limitations. It enhanced their understanding of three-dimensional brain anatomy, boosted enthusiasm, and improved learning efficiency. The workshops supported the students’ progression through the knowledge acquisition phases—understanding, mastery, and application.Conclusion: DSI Studio demonstrates potential as an educational tool in neuroanatomy, offering a supportive and flexible learning environment conducive to achieving learning objectives. Our findings preliminarily support the adoption of DSI Studio’s fiber reconstruction technology in undergraduate medical education.Keywords: neuroanatomy, DSI studio, spatial understanding ability, fiber reconstruction